Case Report : Scabies in a Child with a History of Tuberculosis and Severe Short Stature with Environmental Risk Factors - Aqil Fq Faerobby, Mohammad; Nurrakhma Arum Kurnia, Siti; Arifin, Samsul (Jurnal Ilmu Kedokteran Keluarga, 2025)
Background: Scabies is a contagious skin disease that is a public health problem, especially in environments with poor sanitation and high population density. The condition can be more complex in pediatric patients with comorbidities and significant environmental risk factors. Objective: This case report aims to describe the management of scabies in a 1-year and 7-month-old child with a history of tuberculosis and severe short stature, using a holistic family medicine approach. Method: This study is a case report. Data were obtained through heteroanamnesis with the mother, physical examination, and home visits. A comprehensive assessment was conducted using a holistic diagnosis (five axes), family assessment tools (Genogram, Family APGAR, SCREEM), and the Mandala of Health framework. Results: The patient was diagnosed with scabies (ICD-10 B86) and severe short stature (severely stunted). Significant risk factors identified included a crowded living environment in an extended family, poor housing conditions with inadequate ventilation and sunlight, low socioeconomic status, and exposure to passive smoking from three family members. Comprehensive management included pharmacotherapy (Permethrin 5% cream and Cetirizine syrup) and non-pharmacological interventions focused on the patient, family, and community, including simultaneous treatment for all family members and education on environmental hygiene. Follow-up during home visits showed significant clinical improvement. Conclusion: A holistic and comprehensive family medicine approach that addresses biomedical, individual, family, and environmental factors is essential for the effective management of scabies in vulnerable pediatric patients with complex health and social issues.